Ruthenium Complexes Immobilized on an Azolium Based Metal Organic Framework for Highly Efficient Conversion of CO2 into Formic Acid. Issue 4 (25th January 2019) - Wu, Chao; Irshad, Faisal; Luo, Maowei; Zhao, Yujun; Ma, Xinbin; Wang, Shengping
Abstract: A series of efficient heterogenized ruthenium catalysts designated as Rux‐NHC‐MOF (x=1, 2, 3; NHC=N‐heterocyclic carbene; MOF=metal organic framework) were successfully synthesized by the immobilization of different ruthenium complexes RuCl3, [RuCp*Cl2 ]2 (Cp*=pentamethylcyclopentadienyl) and [Ru(C6 Me6 )Cl2 ]2 (C6 Me6 =hexamethylbenzene) on an azolium based MOF through post‐synthetic metalation. The heterogenized catalysts were subsequently accessed for the catalytic hydrogenation of CO2 to formic acid. The resulting Ru3‐NHC‐MOF catalyst exhibited the highest activity because of its stronger electron‐donating ability of C6 Me6 ligand of [Ru(C6 Me6 )Cl2 ]2 complex, which is favorable for CO2 hydrogenation reaction. A high turnover number (TON) value up to 3803 was obtained at 120 °C under a total pressure of 8 MPa (H2 /CO2 =1) for 2 h with K2 CO3 additive in N, N‐Dimethylformamide (DMF) solvent. Furthermore, the heterogenized Ru3‐NHC‐MOF catalyst was effectively recovered through filtration without significant loss of catalytic activity. Abstract : The Wheel of Fortune turns : Novel Ru‐based heterogenized catalysts are prepared through the immobilization of ruthenium complexes on an azolium MOF. Owing to stronger electron‐donating ability of C6 Me6 ligand of ruthenium complex, a higher turnover number up to 3803 is obtained for the catalytic hydrogenation of CO2 to formic acid, outperforming other heterogeneous systems reported in the literature.